Pengaruh Kinerja Keuangan Terhadap Tingkat Bagi Hasil Deposito Mudharabah Dan Tingkat Pengembalian Ekuitas Pada Bank Umum Syariah Di Indonesia - Moh. Iskandar Nur; Mohamad Nasir (Diponegoro Journal of Accounting, 2014)
This research aims to determine the impact of profitability levels, financing levels, and efficiency levels to return on mudharabah deposit and return on equity. The proxy of profitability levels is return on asset, the proxy of financing levels is financing to deposit ratio, and the proxy of efficiency levels is operating expenses to operating income. While the dependent variable used in this research is return on mudharabah deposit and return on equity.This study used secondary data with entire population of Islamic banks listed in the Indonesia Bank (BI) in 2011-2013. The method used to determine the sample using purposive sampling. The analytical method used is multiple linear regression, regression testing prior to first tested the classical assumptions.The result of this research showed that return on asset (ROA) positive significant with return on mudharabah deposit (ROMD). Other result noted that operating expenses to operating income (BOPO) is negatively significant with return on mudharabah deposit (ROMD), while financing to deposit ratio (FDR) are did not significant with return on mudharabah deposit (ROMD). And the result of this research also showed that return on asset (ROA) affect return on equity (ROE), Operating expenses to operating income (BOPO) is negatively significant with return on equity, While financing to deposit ratio (FDR) are did not significant with return on equity (ROE). Overall it can be concluded from these results that return on asset (ROA), financing to deposit ratio (FDR), and operating expenses to operating income (BOPO) affect return on mudharabah deposito and return on equity.